Kefeektifan Beberapa Jenis Daun Tanaman Sebagai Antifeedant untuk Mengendalikan Kutu Beras (Sitophilus oryzae L.) - Satrio Wicaksono; Akhmad Gazali; Jumar Jumar (Universitas Lambung Mangkurat, 2018)
Rice is a staple food commodity consumed by 95% of Indonesia's population in addition to corn, sago and sweet potato. That rice consumption reached 139.15 kg per capita per year, far exceeding the world average consumption of 60 kg per capita per year. However, the high consumption of rice, not accompanied by a significant increase in rice productivity annually. Generally, post-harvest pests that exist in the deposited material is from the Coleoptera class, one of them is Sitophilus Oryzae L. Pest controls Sitophilus Oryzae L until now still use chemical pesticides and fumigation. Fumigants used in fumigation in Bulog warehouses today consist of Phosphine and Methyl bromide. The use of chemical pesticides in pest control has many negative impacts. The problem of environmental pollution is a clear consequence, besides the use of chemical pesticides in Indonesia has destroyed 55% of pest species and 72% of biological control agents. Therefore, it is necessary to replace environmentally friendly pesticides, One alternative choice is the use of vegetable pesticides. The vegetable pesticide is one of the pesticides which material comes from plants. This research uses Completely Randomized Design (CRD) with one factor. The treatment used in this research is 13 treatments with 3 replications, resulting in 39 units of experimental unit. Unit placement is done randomly on 39 barriers available. The results show that the treatment of repellent and antifeedant plant extracts affected on the population of rice lice and rice damage by rice lice. Plants that are able to make the population of rice lice decline namely Wuluh starfruit with a dose of 50 grams and which is able to reduce the damage of rice that soursop leaves with a dose of 40 grams